Outcome of cataract surgery in juvenile idiopathic arthritis-associated uveitis under two different biological regimens - Mariam R Fadel; Elzanaty Hassan; T Radwa; Sara M Esmat (Delta Journal of Ophthalmology)
Aim In this study, we compared the outcome of cataract extraction in patients with juvenile idiopathic arthritis (JIA)-associated uveitis treated with adalimumab (ADA) compared to patients treated with infliximab (IFX).